S ciprofloksacinom povzročena holestatska okvara jeter - Vujasinović, Miroslav (Zdravniški vestnik, 2012)
Background: Drug-induced liver injury has been described for a large number ofdrugs. It is a common cause of drug withdrawal from the market. Ciprofloxacin is a commonly prescribed fluoroquinolone antibiotic and is a rare cause of hepatotoxicity. To our best knowledge this is the first case of ciprofloxacin-induced cholestatic liver injury in Slovenia. Case report: A 19year old man has been treated with ciprofloxacin at a daily dose of 500 mg twice a day due to a mild respiratory infection. After twenty days he was admitted to hospital because of jaundice. Laboratory findings showed a typicalpattern of acute cholestatic liver failure, which was additionally confirmed by the liver biopsy. The patient was treated symptomatically. Ten months later the patientćs clinical status is stabile with a normal bilirubin level and mildly elevated alkaline phosphatase and gamma-glutamyltransferase. Conclusion: Although severe hepatotoxicity after the administration of ciprofloxacin is rare, physicians should be cautious and alert to its side-effects.
Keywords: Adult; Adverse Effects; bolezni jeter; Chemically Induced; Cholestasis, Intrahepatic; Ciprofloksacin; Ciprofloxacin; drug; Holestaza intrahepatična; jetra; Jetra, bolezni; Liver Diseases; Odrasli; stranski učinki; zdravila